Changes in N‐terminal pro‐B‐type natriuretic peptide levels and outcomes in heart failure with preserved ejection fraction: an analysis of the I‐Preserve study. (29th April 2015) - Jhund, Pardeep S.; Anand, Inder S.; Komajda, Michel; Claggett, Brian L.; McKelvie, Robert S.; Zile, Michael R.; Carson, Peter E.; McMurray, John J.V.
Abstract Aims In patients with heart failure (HF) and reduced ejection fraction, decreases or increases in NT‐proBNP levels are associated with better and worse outcomes, respectively. The association in HF and preserved ejection fraction (HF‐PEF) is unknown. We examined the association between change in level of NT‐proBNP and prognosis in patients with HF‐PEF. Methods and results We examined the association between change in NT‐proBNP from baseline to 6 months and cardiovascular (CV) death or HF hospitalization in 2612 participants in the Irbesartan in Patients with Heart Failure and Preserved Systolic Function Study (I‐Preserve). Change in NT‐proBNP was modelled as a restricted cubic spline in a Cox model after adjusting for baseline NT‐proBNP and known prognostic variables. Median change in NT‐proBNP from baseline was −7 pg/mL (interquartile range −143 to +108). After adjustment, a 1000 pg/mL decrease in NT‐proBNP from baseline was associated with a reduction in the risk of CV death or HF hospitalization [hazard ratio (HR) 0.73, 95% confidence interval (CI) 0.53–1.02]; a 1000 pg/mL increase was associated with an increase in risk (HR 2.01, 95% CI 1.50–2.69). Beyond a 1000 pg/mL rise or fall, there was little additional change in risk. Addition of change in NT‐proBNP at 6 months to a model with only baseline NT‐proBNP improved the C‐statistic from 0.752 to 0.769 (P = 0.013). Conclusion In HF‐PEF, a rise in NT‐proBNP was associated with an increase in risk of CV death or HF hospitalization and a fall was associated with a trend towards a decrease in risk. NT‐proBNP may be a useful marker to monitor prognosis in this condition.